One of the figures of cultural communication between Algeria and Egyptduring the 17th century AD - Yahya Al-Shawi Al-Naili - is a model - mekhalfia, mohamed; belamri, fateh (Journal of Social Sciences and Humanities, 2024)
This study aims to highlight the position enjoyed by Algerian scholars in Egypt, during the Ottoman era, because this country included many cultural centers, which in turn formed a reservoir for various sciences and knowledge. That the Algerian scientists' trips were controlled by many factors and circumstances. This presence of Algerian scholars such as "Yahya Al-Shawi Al-Naeli" in Egypt contributed to the flourishing of the scientific movement through influence and influence, by virtue of the positions and jobs that he assumed, especially in Al-Azhar Al-Sharif, from teaching, issuing fatwas and authoring, as it is a form of one of the stations that Algerian scholars and students visited.